Psychological Predictors of COVID-19 Prevention Behavior in Hungarian Women Across Different Generations - Marschalko, Eszter Eniko; Kotta, Ibolya; Kalcza-Janosi, Kinga; Szabo, Kinga; Jancso-Farcas, Susana (Frontiers in Psychology, 2021)
Background: Age related differences were found in prevention behaviour, showing that older individuals tend to be the most proactive. The aim of the study was the identification of psychological predictors on COVID-19 prevention behaviour in women, across four generations. In addition, the predictive role of the psychological variables was explored through the lens of negative and positive information processing perspective on total and domain-specific COVID-19 prevention behaviour. Methods: A cross-sectional research was conducted. The sample included 834 Hungarian speaking women. The assessed variables were: COVID-19 knowledge, risk perception, COVID-19 health anxiety, negative automatic thoughts, psychological flexibility and four domains of COVID-19 prevention behaviour (social distancing, general hygiene, information seeking, health behaviour). A three-level hierarchical linear regression analysis was conducted to investigate the predictors of preventive behaviour in each generation. Results: A diversity across generations was found. In case of baby boomer generation, the final model explained 32.4% of the variance for total prevention behaviour (F (14,215) = 8.847, p < .001), and only perceived risk made a significant contribution. For Gen X the final model accounted for 21.1% of variance of total prevention behaviour (F (14,341) = 7.788, p < .001), marital status, perceived risk, COVID-19 health anxiety and negative automatic thoughts made significant contributions. In case of Gen Y the final model accounted for 6.2 % of variance on total prevention behaviour (F (14,147) = 1.761, p = .05), only perceived risk had a contribution to the final model. For Gen Z the final model accounted for 23.4% of variance on total preventive behaviour (F (13,71) = 2.979, p = .002), and only psychological flexibility made a contribution to the model. The results on the distinct domains of COVID-19 prevention behaviour emphasized details in the dissimilarity among generations. Conclusions: The role of generational identity on COVID-19 prevention behaviour is relevant. The coexistence of negative and positive information processing may have its beneficial role in certain areas of prevention.